What was the global burden of kidney cancer attributable to high body mass index from 1990 to 2019? There existed some points noteworthy - Yao, Xue; Luo, Xiao-yan; Tai, Yang-hao; Wang, Kang; Shang, Ji-wen (Frontiers in Nutrition, 2024)
Purpose: With the prevalence of high body mass index (HBMI) increasing over the past thirty years, it is essential to examine the impact of obesity on kidney cancer. This study aims to explore the attributable burden of kidney cancer associated with HBMI and its proportion at different levels. Methods and materials: The data used in this research was obtained from the Global Burden of Diseases Study 2019. We utilized DisMod-MR 2.1, a Bayesian meta-regression tool, to estimate the burden of kidney cancer attributable to HBMI, which was measured by age-standardized mortality rate (ASMR) and age-standardized disability-adjusted life years rate (ASDR). Correlation analysis was conducted by the Spearman rank order correlation method. The temporal trends were analyzed by estimating the estimated annual percentage change (EAPC). Results: Globally in 2019, there were a total of 31.7 thousand deaths and 751.89 thousand disability-adjusted life years (DALYs) attributable to kidney cancer caused by HBMI, increased by 183.1% and 164% respectively. Over the period from 1990 to 2019, the burden of kidney cancer attributable to HBMI increased in all regions, with the most significant increases occurring in Low-middle socio-demographic index (SDI) and Low SDI regions. At the national level, countries with lower SDI had lower ASMR and ASDR compared to developed nations. However, the EAPC values, which indicate the rate of increase, were significantly higher in these countries than in developed nations. Furthermore, across all years from 1990 to 2019, males experienced a greater and more rapidly increasing burden of kidney cancer attributable to HBMI than females. Conclusion: As the population grows and dietary patterns shift, the burden of kidney cancer attributable to HBMI is expected to become even more severe. Males and developed regions have borne a heavier burden from 1990 to 2019. However, the EAPC values for both ASMR and ASDR were higher in males but not in regions with higher SDI values.